HAK KEWARISAN ANAK LUAR NIKAH BERDASARKAN HUKUM ISLAM DENGAN UNDANG-UNDANG PERKAWINAN No.1/1974 - Chairan, A. Tenripadang (DIKTUM: Jurnal Syariah dan Hukum, 2014)
This article describes the inheritance rights of children comparative law outside marriage under Islamic law with marriage law No. After the Constitutional Court Decision 1/1974 of the Test Matril Marriage Act. The approach used is a normative juridical. Based on the results obtained by the understanding that the discussion is based on Islamic law does not justify the right heir to the child outside marriage (zina), to have a child outside marriage only nasab with his mother. However, based on the Constitutional Courts decision that a child outside of marriage will actually occupy an equal footing with legitimate children in terms of inheritance, if the heir just leaving heirs only child outside marriage.